Peranan Sekuen Axial T1 Dual Echo dan IDEAL-IQ dalam Menilai Fatty Liver pada Pemeriksaan MRI Upper Abdomen - Ravenska Novinda Difa Difa (Poltekkes Kemenkes Semarang, 2026)
Background: Epidemiologically, fatty liver disease is one of the most common liver disorders worldwide. The severity of fatty liver is classified based on the proportion of hepatocytes containing fat, with categories ranging from normal to mild, moderate, and severe. In relation to which, Magnetic Resonance Imaging (MRI) is a reliable modality for the detection and quantification of fatty liver and demonstrates higher diagnostic accuracy compared with CT and ultrasound. The T1 dual-echo sequence is used as a qualitative method for assessing fatty liver based on radiologist interpretation, whereas the IDEAL IQ sequence serves as a quantitative method by providing proton density fat fraction (PDFF) values. Methods: This research was undertaken at Radiology Department of Soedirman National Defence Central Hospital starting from September up to November 2025. This research applied a descriptive quantitative study design which was employed using observation and questionnaire methods. A total of 20 samples were accordingly included, and all participants underwent the same imaging protocol, consisting of axial T1 dual-echo and IDEAL IQ sequences during upper abdominal MRI examinations. The agreement in fatty liver severity assessment between the two sequences was subsequently analysed using Cohen’s Kappa statistical test. Results: Using the axial T1 dual-echo sequence as a qualitative method and the IDEAL-IQ sequence as a quantitative method, fatty liver assessment was obtained across all severity categories. Conclusions: This research demonstrates that there is a significant agreement between the assessment of fatty liver severity using the axial T1 dual- echo sequence and the IDEAL IQ sequence. Therefore, it can be concluded that the both methods produce highly consistent and reliable evaluations and are justifiable for clinical use.